2012
DOI: 10.1007/s12663-012-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Normal Mouth Opening in an Adult Indian Population

Abstract: Background Mouth opening among different population has been shown to vary considerably and its range is specific for a given population. The present study is an attempt to calculate the normal mouth opening in adult Indian population. Method A total of 894 adults, 463 males and 431 females, in the age range of 21 to 70 years were studied. The subjects were asked to open their mouth maximally till no further opening was possible. The distance from the incisal edge of the upper incisor teeth to the incisal edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 13 publications
0
33
0
6
Order By: Relevance
“…In the paediatric and adolescent population, the mandibular mobility increases with somatic growth and age‐related normative values of mandibular mobility are influenced by factors such as age, gender, weight, height and ethnicity . Several publications exist on the topic of mandibular mobility capacity in paediatric and adolescent cohorts ; however, differences in patient sampling (age and number of included individuals) and the methods used for the assessment of mandibular mobility makes inter‐study comparisons difficult. Often, the population‐based values have been reported to provide a frame of reference for comparison of the individual patient to normative values of the population.…”
Section: Introductionmentioning
confidence: 99%
“…In the paediatric and adolescent population, the mandibular mobility increases with somatic growth and age‐related normative values of mandibular mobility are influenced by factors such as age, gender, weight, height and ethnicity . Several publications exist on the topic of mandibular mobility capacity in paediatric and adolescent cohorts ; however, differences in patient sampling (age and number of included individuals) and the methods used for the assessment of mandibular mobility makes inter‐study comparisons difficult. Often, the population‐based values have been reported to provide a frame of reference for comparison of the individual patient to normative values of the population.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Khare et al . . found that the typical mouth opening is of 56·7 ± 7·2 for males aged between 21 and 30 years old, and 57·1 ± 6·5 for males aged between 31 and 40 years old.…”
Section: Methodsmentioning
confidence: 95%
“…The mouth opening was limited significantly to 12 mm. [11] The CT revealed areas of destruction within the right mandibular condyle [ Figure 2] and MRI shows diffuse soft tissue thickening with abscess formation [ Figure 3]. The histopathological examination of the abscess cavity wall revealed cells consistent with mycobacterial tuberculosis infection which led to the eventual diagnosis.…”
Section: Discussionmentioning
confidence: 99%